Nilai-Nilai Pendidikan Akhlak dalam Kitab Al-Qaul Al-Jaliy - Aulia, Novira; Fattah, Abdul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to explore the moral education values embedded in Al-Qaul Al-Jaliy by Sheikh Muḥammad bin Ziyād ‘Ālam ad-Dīn dan Muḥammad bin ‘Alī al-Aṭrash and to analyze the methods of value transmission within the context of Islamic education. Employing a qualitative descriptive approach and content analysis, the research identified core values including sincerity (ikhlas), honesty (sidq), humility (tawadhu’), patience and gratitude, respect toward teachers and knowledge, as well as consistency (istiqamah) and responsibility. These values are conveyed through exemplary modeling, habituation, dialogue, and emotional bonding between teachers and students. The findings reveal that this classical Islamic text not only offers deep ethical insights but also provides a pedagogical framework that remains highly relevant in addressing the moral crisis in today’s educational landscape.